Cerebral White Matter Myelination and Relations to Age, Gender, and Cognition: A Selective Review - Buyanova, Irina S.; Arsalidou, Marie (Frontiers in Human Neuroscience, 2021)
White matter makes up about fifty percent of the human brain. Maturation of white matter accompanies biological development and undergoes the most dramatic changes during childhood and adolescence. Despite the advances in neuroimaging techniques, controversy concerning spatial and temporal patterns of myelination, as well as the degree to which the microstructural characteristics of white matter can vary in a healthy brain as a function of age, gender and cognitive abilities still exists. In a selective re-view we describe methods of assessing myelination and evaluate effects of age and gender in six major fiber tracts, highlighting their role in higher-order cognitive functions. Our findings suggests that mye-lination results vary by age, fiber tract and hemisphere. Effects of gender were also identified, although some attribute differences to methodological factors or social and learning opportunities. Findings point to further directions of research that will improve our understanding of the complex myelination-behavior relation across development that may have implications for educational and clinical practice.